Co-morbidity and blood group type risk in coronavirus disease 2019 patients: A case-control study - Mohammed Badedi; Ali Makrami; Awaji Alnami (Elsevier, 2021)
Objective: The objective of the study was to assess mortality risk associated with co-morbidities and blood group type in coronavirus disease 2019 (COVID-19) patients in Jazan, Saudi Arabia. Methods: This case-control study enrolled 323 Saudi adults with COVID-19, confirmed by real-time reverse transcription-polymerase chain reaction. The participants were selected randomly between August 31, 2020, and July 1, 2020, from the Health Electronic Surveillance Network system, which contains the primary data on COVID-19 infections in Jazan, Saudi Arabia. The sample included 108 patients who died due to COVID-19 disease and 215 controls who recovered from it (1:2 ratio). The chi-square test, independent samples t-test, and logistic regression were used to perform the statistical analysis. Results: Mortality was higher in older age patients with COVID-19 (mean = 65.4 years, standard deviation [SD] = 15.6) compared to recovered patients (mean = 39.5 years, SD = 14.8) (p < 0.001) with a moderate effect size (eta squared = 0.06). Diabetes mellitus (odds ratio [OR] = 9.4), hypertension (OR = 8.6), cardiovascular disease (OR = 7.4), chronic kidney disease (OR = 3.3), and obesity (OR = 2.0) were significantly associated with death due to COVID-19. Using logistic regression analysis, older age and diabetes mellitus were the primary independent predictors of COVID-19 mortality. However, there was no significant association between a specific ABO blood group and mortality risk (P = 0.07). Conclusion: Older age and the presence of co-morbidities, especially diabetes mellitus, increased the risk of death in patients with COVID-19. Establishing the causality of death in patients with COVID-19 should be a key aim of future studies.